Developing Online Construction Technology Resources in Tectonic Design Education - Ham, J.; Schnabel, M.; Datta, Sambit (Optus VDI, 2012)
We outlined issues of importance in relation to tectonic design within the architectural profession and the relationship to architectural education in Australia. Twelve years of research and curriculum development at Deakin University is discussed, involving the creating of online resources and case studies, digitally-integrated projects relating to building construction and design studio education. The ethos behind the Construction Primer of engaging students as 'amateur researchers' in a way that ensures 'that student research work is worth more than course assessment' forms that pedagogical foundation of much of this work. A model of Socially Networked Construction Technology education has been developed that integrates social networks and the Internet to engage students in tectonic design within and outside the classroom through authentic curricula. Through the use of Virtual Galleries, Blogs, YouTube and social networks, a culture of peer learning and sharing has been developed. Through shared knowledge facilitated through social networks, great potential lies for expanding the synergies between higher order learning and online resource developed for design decision support.